Synthesis and Electroluminescence Characterization of Cadmium Complex - Rahulkumar; K. Singh; R. Srivastava; M.N. Kamlasanan (Журнал нано- та електронної фізики)
We have synthesized and characterized a new electroluminescence material,Cadmium [(2-(2-hydroxyphenyl)benzoxazole)(8-hydoxyquinoline)] Cd(HPB)q. The absorption spectra of this material show maxima at 378 nm. It may be attributed due to π° – π* transition. The photoluminescence showed peak at 520 nm. TGA data of the material shows stability up to 370 °C .Organic light emitting diode have been fabricated with this material and the fundamental structures of the device is ITO/α-NPD/ Cd(HPB)q/BCP/Alq3/LiF/Al exhibited a luminescence peak at 550 nm. The maximum luminescence of the device was 295 cd/m2 with current density of 6687 A/m2 at 20 V. The maximum current efficiency of OLED was 1.01 cd/A at 17 V and power efficiency was 1.01 lm/w at 17 V.